EKSISTENSI PONDOK PESANTREN NURUL WATHAN PASAR KEMBANG DALAM PENDIDIKAN ISLAM DI KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR TAHUN 1960-2017 - Hasnidar Hasnidar; Ridwan Melay; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Nurul Wathan Pasar Kembang Islamic Boarding School is the oldest boarding school in Keritang Subdistrict, Indragiri Hilir Regency which was built by K.H. Abdurrahman Yaqoeb in 1960 in Pasar Kembang village.The Nurul Wathan Pasar Kembang boarding school was originally built since many of the people in Pasar Kembang village went astray from Islamic teachings.To find out the existence of Nurul Wathan Pasar Kembang Islamic Boarding School in Islamic education. The method used is a qualitative method, which is by collecting resources not obtained from statistical procedures or other forms of calculation.This type of research is a field research to explore and examine data relating to the title. The respondents from the research were the foundation leaders, teachers and alumni of the Pasar Kembang Islamic Boarding School Nurul Wathan.The technique used in data by interview and documentation. Based on the results of the study it can be concluded that the Nurul Wathan Islamic Boarding School Pasar Kembang is able to maintain the existence in the circle of the keritang community in Islamic education.Keyword: Existence, Nurul Wathan, Keritang, Islamic Education